Direct comparison of galactomannan performance in concurrent serum and bronchoalveolar lavage samples in immunocompromised patients at risk for invasive pulmonary aspergillosis - Boch, Tobias; Buchheidt, Dieter; Spiess, Birgit; Miethke, Thomas; Hofmann, Wolf-Karsten; Reinwald, Mark (Mycoses, 2016)
Invasive pulmonary aspergillosis (IPA) is a life-threatening infection mainly affecting immunocompromised patients. Early diagnosis is critical, but the diagnostic gold standard (histopathology and culture) is time consuming and cannot offer early confirmation of IPA. Fungal biomarkers like galactomannan (GM) are a promising extension to the diagnostic repertoire. However, it still remains under discussion if biomarker analysis from the site of the infection is superior to testing blood samples. We retrospectively evaluated the diagnostic performance of concurrent serum GM and bronchoalveolar lavage (BAL) GM (obtained within 24 h) of immunocompromised patients at high risk of IPA. Twenty-six proven/probable patients and eight patients with no IPA according to the EORTC/MSG 2008 criteria were included in this study. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic odds ratio were for BAL GM: 85%, 88%, 96%, 64% and 38.5, and for serum GM: 23%, 88%, 88%, 26% and 2.1 respectively. BAL GM proved to be significantly more sensitive for the detection of IPA compared to same-day serum GM in patients at high risk of IPA (P < 0.0001). Our data show that BAL GM testing is significantly superior to serum GM implying that diagnostic efforts should focus on specimens from the site of infection.
Gesehen am 23.01.2019
First published: 02 December 2015